Evaluation of Early Childhood Literacy Strengthening Strategy in Sub-district The Land of the Rising Sun Regency Cilacap - Suparti; Mulyani , Petra Kristi (JURNAL PENDIDIKAN USIA DINI, 2025)
This study aims to evaluate literacy strengthening strategies in Early Childhood Education (ECED) using the CIPPO (Context, Input, Process, Product, Output) model approach. The focus of the research is to analyze the effectiveness of the strategy implementation in creating a learning environment that supports children's literacy development. This research used a qualitative descriptive method. The research subjects consisted of principals and teachers from two PAUD institutions in Kawunganten sub-district, Cilacap district, namely SBB Bustan El Firdaus and SBB Kartini 01. Data collection techniques included semi-structured interviews, direct observation of learning activities and documentation of activities. Data were analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing and verification. Data triangulation was conducted to ensure the validity of the results. The results showed that the literacy reinforcement strategy was well implemented. PAUD institutions are able to create a text-rich, social-emotionally supportive environment and a conducive academic environment. However, there are two input aspects related to human resources and one output aspect that still need improvement, especially in involving the home and community as part of the literacy ecosystem. The implications of this study suggest that the success of literacy programs in early childhood education depends not only on classroom strategies but also on the active involvement of parents and communities. The findings can serve as a basis for developing more holistic education policies and practices in the future.